Robust uplink power control algorithm for multimedia CDMA cellular systems - GU Hong-yu; YANG Chen-yang (Tongxin xuebao)
Robust uplink power control problem in multimedia CDMA cellular systems containing both QoS-guaranteed （QG） and best-effort （BE） traffics was investigated. Taking the traffic burstiness, the link gain estimation error and other cell interference into account, the outage probability was derived and a nonlinear iterative algorithm （NIA） was obtained. Given a data rate allocation profile for BE traffics, the NIA could determine whether the link reliability of both QG and BE traffics could be guaranteed by power control. Based on the proposed NIA, the power and rate control algorithms （PRCAs） was further developed for multimedia CDMA systems supporting continuous and discrete data rate, respectively. Finally, the convergence of the proposed NIA was validated and the performance advantage of the proposed PRCAs was shown to a suboptimal algorithm by simulation.